Healthcare workers` motivation in preventive activities - Trifunović, Boban; Fišeković Kremić, Marina (General Practice, 2023)
Introduction. Successful implementation of all activities,especially in the area of preventive medicine, healthcareinstitutions may accomplish only if their employees are highlymotivated and properly rewarded for their work. The bestmotivational system should be designed so the employees getthe rewards that matter to them. That is why research intothe motives and needs of employees appears as a necessaryprerequisite for the effectiveness of motivation.Objective. We aimed at examining the most importantmotivational factors for preventive activities in healthcareworkers.Method. The research was conducted, as a case study,in the Primary Healthcare Center (PHC), Golubac from December2019 to December 2020. We analyzed the results ofthe preventive activities of healthcare workers from the PHCGolubac during project activities in 2020 and compared themto the results from 2018. Employees` attitudes towards motivationalfactors were analyzed based on the conducted individualinterviews and surveys.Results. The results of preventive actions in 2020,through project activities, were significantly better than thosein 2018. The diabetes screening response was 42%, the realizationof blood pressure measuring in diabetic patientswas 58%, and HbA1c was measured in 34% of diabetics in2020. In 2018 screening realization was 15%, blood pressurewas measured in 50% of diabetics, and HbA1C in 10%. Themost important motivational factors for healthcare workerswere the importance of preventive activities for the people`shealth, the participation of the manager as the project leader,the equipment gained during the project that will improvetheir work, clearly defined goals, and personal responsibilityfor the project`s success.Conclusion. The motivation of healthcare workersis of great importance for the successful implementation ofpreventive activities. Our research provides information forhealthcare managers on ways to improve their employees`motivation.Keywords: motivation,
Keywords: motivation; healthcare workers; prevention; project activities